Development of an Electronic Job Sheet for Forward-Reverse Circuits in The Electrical Installation Technology Program - Mega Risna; Sukardi; Arwizet K; Elfizon; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2026)
The practicum learning process in vocational education requires instructional media that support students in understanding work procedures systematically and independently. However, the printed jobsheets used in forward-reverse circuit learning still have limitations in visualization and interactivity. This study aims to develop an electronic jobsheet (e-jobsheet) for forward-reverse circuit materials and determine its validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the Instructional Development Institute (IDI) model, consisting of three stages: define, develop, and evaluate. The participants included expert validators, subject teachers, and 30 eleventh-grade students in the Electrical Power Installation Engineering program. Data were collected through observations, interviews, questionnaires, and learning outcome tests. The findings revealed that the developed e-jobsheet achieved material validity of 75% (valid), media validity of 85.93% (very valid), and language validity of 94.65% (very valid). The practicality test showed a score of 91.67% (very practical). In addition, the effectiveness test indicated an improvement in student learning outcomes, with the average pretest score increasing from 55 to 88.1 in the posttest and producing an N-gain score of 0.78 in the high category. Therefore, the developed e-jobsheet is considered valid, practical, and effective for supporting digital-based and student-centered practicum learning in forward-reverse circuit materials.